Analysis of Visitors' Perceptions of California Cialam Jaya Agrotourism in Tanea Village, Konda District South Konawe Regency - Goretti, Maria; Fyka, Samsul Alam; Sadimantara, Fahria Nadiryati (International journal of technology and education research, 2026)
This study aims to analyze visitor perceptions of the California Cialam Jaya Agrotourism Site located in Tanea Village, Konda District, South Konawe Regency. Visitor perceptions were analyzed based on four indicators: accessibility, supporting facilities, tourist attractions, and service quality. This study used a qualitative descriptive method with a survey approach of 48 respondents selected using random sampling. Data were collected through observation, interviews, and questionnaires, then analyzed using a Likert scale to measure visitor perceptions. The results showed that visitor perceptions of all indicators were in the (Agree) category. Accessibility received the highest average score of 2.64, indicating easy access to the tourist site. Supporting facilities received an average score of 2.50, tourist attractions 2.70, and service quality 2.62. This indicates that the California Cialam Jaya Agrotourism area has been able to provide a good tourism experience for visitors, although there are still areas for improvement, such as directional signage and public facility maintenance